Variation in cytokine genes can contribute to severity of acetabular osteolysis and risk for revision in patients with ABG 1 total hip arthroplasty: a genetic association study - Gallo, Jiri; Mrazek, Frantisek; Petrek, Martin (BMC medical genetics, 2009)
BACKGROUND: The differences in total hip arthroplasty (THA) survivorship may be influenced by individual susceptibility to periprosthetic osteolysis. This may be driven by functional polymorphisms in the genes for cytokines and cytokine receptors involved in the development of osteolysis in THA, thereby having an effect on the individual's phenotype. METHODS: We performed a study on 22 single-nucleotide polymorphisms (SNPs) for 11 cytokines and two cytokine receptor candidate genes for association with severity of acetabular osteolysis and risk to failure in THA. Samples from 205 unrelated Caucasian patients with cementless type THA (ABG 1) were investigated. Distribution of investigated SNP variants between the groups of mild and severe acetabular osteolysis was determined by univariate and multivariate analysis. Time-dependent output variables were analyzed by the Cox hazards model. RESULTS: Univariate analysis showed: 1) TNF-238*A allele was associated with severe osteolysis (odds ratio, OR = 6.59, p = 0.005, population attributable risk, PAR 5.2%); 2) carriers of the IL6-174*G allele were 2.5 times more prone to develop severe osteolysis than non-carriers (OR = 2.51, p = 0.007, PAR = 31.5%); 3) the carriage of IL2-330*G allele was associated with protection from severe osteolysis (OR = 0.55, p = 0.043). Based on logistic regression, the alleles TNF-238*A and IL6-174*G were independent predictors for the development of severe acetabular osteolysis. Carriers of TNF-238*A had increased cumulative hazard of THA failure according to Cox model (p = 0.024). In contrast, IL2-330*G allele predicted lower cumulative hazard of THA failure (p = 0.019). CONCLUSION: Genetic variants of proinflammatory cytokines TNF-alpha and IL-6 confer susceptibility to severe OL. In this way, presence of the minor TNF allele could increase the cumulative risk of THA failure. Conversely, SNP in the IL2 gene may protect carriers from the above THA complications.
Keywords: alely; Polymorphism, Single Nucleotide; proporcionální rizikové modely; Humans; selhání protézy; genetické asociační studie; lidé středního věku; Proportional Hazards Models; receptory cytokinové; interleukin-2; cytokiny; jednonukleotidový polymorfismus; Arthroplasty, Replacement, Hip; rizikové faktory; Aged; dospělí; Female; Interleukin-6; náhrada kyčelního kloubu; Alleles; senioři; lidé; osteolýza; Interleukin-2; TNF-alfa; Osteolysis; Adult; ženské pohlaví; stupeň závažnosti nemoci; Genetic Association Studies; Male; interleukin-6; Middle Aged; Cytokines; Prosthesis Failure; Odds Ratio; Receptors, Cytokine; Severity of Illness Index; Tumor Necrosis Factor-alpha; mužské pohlaví; odds ratio; Risk Factors